Changes in the auroral electrojet currents inferred from geomagnetic field variations at Maitri and northern conjugate station - Kalra, Rajesh; Dhar, Ajay; Nair, K.U.; Jeeva, K.; Daga, D.M.; Rajaram, G. (1995)
Behaviour of geomagnetic variations over Maitri station, Antarctica through a calm to moderately calm and finally into a highly disturbed day, has been recorded. The data has been synthesized against similar observations made in two observatories nearest and equidistant from a point in northern hemisphere which is conjugate to Maitri in southern hemisphere.